Solve for p a=p(1+rt)

Math
a=p(1+rt)
Rewrite the equation as p(1+rt)=a.
p(1+rt)=a
Divide each term by 1+rt and simplify.
Tap for more steps…
Divide each term in p(1+rt)=a by 1+rt.
p(1+rt)1+rt=a1+rt
Cancel the common factor of 1+rt.
Tap for more steps…
Cancel the common factor.
p(1+rt)1+rt=a1+rt
Divide p by 1.
p=a1+rt
p=a1+rt
p=a1+rt
Solve for p a=p(1+rt)

Meet the Team our Math Expers

Our Professionals

Robert Kristofer

Anna Frok

Magnus Flores

Lydia Fran

We are MathExperts

Solve all your Math Problems: https://elanyachtselection.com/

We can solve all your math problems
Scroll to top